Influence of chloroquine on kinetics of single-cell gel electrophoresis - Zazhytska, M.O.; Afanasieva, K.S.; Chopei, M.I.; Vikhreva, M.A.; Sivolob, A.V. (Вiopolymers and Cell, 2012)
In single-cell gel electrophoresis (the comet assay) the DNA of lysed cells, the nucleoids, extends towards the anode in a track resembling a comet tail. The aim of this work was to investigate the effects of changes in DNA topology on this process. Methods. We used the kinetic approach, proposed earlier by us, to measure a relative amount of DNA in the comet tails as a function of time in the presence of different concentrations of chloroquine, a widely used intercalator. Results. We have shown that, at given small concentrations, intercalation of chloroquine strongly facilitates the comet tail formation. At the same time, some part of DNA (about 8 %) in the nucleoids exits very fast independently on chloroquine, while the largest part of DNA (about three quarters) does not exit at all. At high concentrations the intercalator increases the fraction of DNA, which cannot exit. Conclusions. Our results imply that the loop domains, which contain about one to several hundreds kilobases, represent only a small part (about a quarter) of DNA in the nucleus. The intercalation induces detachment of these loops from the nuclear matrix. Keywords: comet assay, chloroquine, intercalation, DNA loops, supercoiling.